PENERAPAN METODE EXACT MATCH PADA APLIKASI ALQUR’AN DAN HADITS BERBASIS ANDROID - Suardi, Citra; Wibawa, Aji Prasetya; Hasanuddin, Tasrif; Mude, Muhammad Aliyazid; Cokrowibowo, Sugiarto (ILKOM Jurnal Ilmiah, 2019)
Exact Match is used to bring up sentences only on certain keywords. This study aims to apply the Exact Match method in the Al-qur'an and Hadith applications to find conformity between verses and hadiths. This research simplify for the people to increase their knowledge of the Qur'an and Hadith. This study uses interview techniques for some Muslims regarding the need to learn the quran and the hadith, observation technique is to do a comparison of several hadiths by asking for recommendations from the ustadz/ustazah, identify what are the shortcomings of existing hadith applications, and literature study techniques that are collecting data obtained from the Qur'an and the Hadith. The results of this study are (1) Created an application to match Hadiths that are in accordance the verse with the Exact Match method (2) Showing hadith related to the contents of the selected verse (3) Speed to produce a match in the Application of the Qur'an and Hadith depends on the internet network and the amount of data (4) The number of hadiths that appear is influenced by the number of available hadiths.